Cerebrospinal fluid L-lactate as a diagnostic marker for infectious-inflammatory disorders in the central nervous system of cattle - Ferrini, Sara; Cagnotti, Giulia; Ala, Ugo; Avilii, Eleonora; Bellino, Claudio; Biasibetti, Elena; Borriello, Giuliano; Corona, Cristiano; Di Muro, Giorgia; Iamone, Giulia; Iulini, Barbara; Pezzolato, Marzia; et al. (Frontiers in Veterinary Science, 2024)
IntroductionBacterial infection of the central nervous system (CNS) poses a clinical challenge and is a leading cause of neurological disorders in cattle. Human studies have demonstrated an increase in cerebrospinal fluid (CSF) L-lactate levels in bacterial meningitis. The aims of this study were to establish a Reference Interval (RI) for L-lactate in bovine CSF and assess its potential as a biomarker for detecting infectious-inflammatory disorders.MethodsCSF L-lactate was measured in the field using a commercially available lactate monitor. The RI for CSF L-lactate was calculated on healthy animals; univariate and receiver operating characteristic (ROC) analyses were performed to disclose an association between CSF L-lactate levels and interpretation of CSF in sick animals.ResultsTwenty-seven healthy cattle and 86 sick cattle with either CNS infectious-inflammatory disorders (47/86) or CNS disorders of other etiology (39/86) were included in this prospective study. The RI for CSF L-lactate was 1.1–2.4 mmol/L. The concentration was higher in the cattle with neutrophilic pleocytosis and the area under the ROC curve was 0.92 compared to other animals. Based on a cut-off of 3.15 mmol/L, CSF L-lactate had diagnostic sensitivity and specificity for neutrophilic pleocytosis of 93 and 80%, respectively.DiscussionThis is the first study to determine a RI for CSF L-lactate in cattle. Elevated CSF L-lactate levels indicated neutrophilic pleocytosis, which is often manifested in acute bacterial infection. The present findings may aid in diagnosis and correct use of antimicrobial drugs.